Effects of Dietary Microbial Muramidase on the Growth, Liver Histoarchitecture, Antioxidant Status, and Immunoexpression of Pro-Inflammatory Cytokines in Broiler Chickens - Anaam E. Omar; Ghada I. Abd El-Rahman; Ahmed Gouda; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Samar A. Abdo; Azhar Eltanahy; Ahmed Said Kamal; Simon J. Davies; Shimaa A. Amer (Animals, 2023)
The impact of microbial muramidase (MMUR) addition to broiler chicken rations was evaluated through growth parameters, liver histoarchitecture, antioxidant status, biochemical analysis, and expression of pro-inflammatory cytokines for 35 days. Four hundred three-day-old chicks (97.68 ± 0.59 g) were distributed to four distinct groups with ten duplicates each (100 chicks/group) consisting of: group 1 (G1): a basal diet without MMUR (control group); G2: a basal diet + 200 mg MMUR kg−1 G3: a basal diet + 400 mg MMUR kg−1; and G4: a basal diet + 600 mg MMUR kg−1. The results showed that the final body weight and total weight gain were increased (p = 0.015) in birds fed with diets supplemented with MMUR at 600 mg kg−1. The feed conversion ratio (FCR) was improved in all treatment groups compared with the control group. Birds fed with a diet supplemented with 600 mg MMUR kg−1 showed the highest body weight gain and improved FCR. The values of thyroxin hormones and growth hormones were increased in all MMUR-supplemented groups. Dietary MMUR increased the activities of antioxidant enzymes (total antioxidant activity, catalase, and superoxide dismutase) and decreased the activity of malondialdehyde (p < 0.05). In addition, it increased the values of interleukin 1 beta and interferon-gamma compared with the control group. Furthermore, dietary MMUR increased the expression of transforming growth factor-beta immunostaining in the liver and spleen tissues. Our results show that supplementing broilers’ diets with 600 mg MMUR kg−1 could enhance the chicken growth rate and improve their antioxidant, inflammatory, and anti-inflammatory responses.